2014
DOI: 10.9790/1959-03246367
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the knowledge and attitude of nurses regarding management of patient with depression in a selected general hospital at Tumkur, Karnataka

Abstract: Depression is one of the common and most affected worldwide public health problems. Depression is an illness that not only involves the mood and thought of a person but also the whole body. Depression is a major cause for premature death and disabilities throughout the world. The high prevalence of suicide is closely associated with depression. Every person usually suffers with depression during their life time. But the degree may be from mild to severe. Method: The research approach used for the study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Another study found that 60% nurses had insufficient knowledge to manage patients with depression. 30 However, other studies indicated that nurse practitioners in a primary care setting 31 and advanced practice nursing students 32 had better scores on knowledge about late-life depression. A study that examined the effectiveness of a training program on nurses’ knowledge of, attitudes toward, and practice changes concerning late-life depression also indicated that primary care nurses’ late-life depression knowledge improved after the training program from 8.25 (68.75% correct answers) to 10.73 (89.42% correct answers).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another study found that 60% nurses had insufficient knowledge to manage patients with depression. 30 However, other studies indicated that nurse practitioners in a primary care setting 31 and advanced practice nursing students 32 had better scores on knowledge about late-life depression. A study that examined the effectiveness of a training program on nurses’ knowledge of, attitudes toward, and practice changes concerning late-life depression also indicated that primary care nurses’ late-life depression knowledge improved after the training program from 8.25 (68.75% correct answers) to 10.73 (89.42% correct answers).…”
Section: Discussionmentioning
confidence: 97%
“…One study revealed that more than half of the nurses expressed an unfavorable attitude toward managing patients with depression, and only 15% of nurses showed a favorable attitude about depression management. 30 Similarly, Scheerder et al 35 found that nurses had more negative attitudes toward depression than physicians and mental health professionals in 9 countries. One recent study also reported that primary health care providers including pharmacy attendants, general practitioners, social workers, and nurses had negative views regarding depression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation